Workplace Happiness: A Research on the Effects of Workplace Environment and Psychological Capital - Ahmet Erkuş; Mine Afacan Fındıklı (Istanbul Management Journal)
Previous studies carried out within the scope of positive psychology reveal that happiness have been related to workplace productivity and the performance of the employees. To widen this insight, this study analyzes the relation between the workplace happiness level of the employees and the psychological capital and also workplace environment variables such as role ambiguity, role conflict, the characteristics of the job, workload, and supervisor support. According to the study results, psychological capital, job characteristics and supervisor support affect the employees’ workplace happiness significantly and positively whereas role ambiguity and role conflict affect them negatively. On the other hand, it is determined that psychological capital has a moderating effect on the relationship between role ambiguity, job characteristics, and supervisor support, and workplace happiness.